The antioxidant 2, 6-di-tert-butylphenol moiety attenuates the pro-oxidant properties of the auranofin analogue. Issue 3 (5th February 2018) - Shpakovsky, D. B.; Shtil, A. A.; Kharitonashvili, E. V.; Tyurin, V. Yu.; Antonenko, T. A.; Nazarov, A. A.; Osipova, V. P.; Berberova, N. T.; Foteeva, L. S.; Schmidt, C.; Ott, I.; Milaeva, E. R.
Abstract : Metal-based drugs are gaining momentum as a rapidly developing area of medicinal inorganic chemistry. Abstract : Metal-based drugs are gaining momentum as a rapidly developing area of medicinal inorganic chemistry. Among gold pharmaceuticals, auranofin is a well known antirheumatic drug. The efficacy of gold–organic complexes largely depends on their pro-oxidant properties since auranofin targets the redox enzyme thioredoxin reductase (TrxR). However, an uncontrollable oxygen burst may be harmful for healthy cells; therefore, the search for chemical modifications to attenuate oxidation-related general toxicity of gold containing anti-inflammatory drugs is justified. In this study, we demonstrate that the incorporation of a specific antioxidant phenol fragment can counterbalance the pro-oxidative potential of the Au containing complex molecule. The electrochemical studies of AuPPh3 SR (1, R= 3, 5-di- tert -butyl-4-hydroxyphenyl) and its precursors AuPPh3 Cl (2 ) and RSH (3 ) showed that complex1 and phenol3 efficiently scavenged the radicals (as detected by cyclic voltammetry) whereas2 had no effect. Compound1 inhibited TrxR in vitro with IC50 0.57 ± 0.15 μM, a value one order of magnitude bigger than the potency reported for auranofin. Compound1 (5 mg kg −1 daily gavage for 14 days) caused a decrease in ex vivo spontaneous and ascorbate-induced lipid peroxidation in the homogenates of rat lung, heart muscle, spleen, liver, kidneys, testicles and brain as assessed by the thiobarbituric acid reactive substances. Importantly, in animals fed with1, no discernible general toxicity was registered suggesting that this compound is well tolerated. Our results provide evidence for an efficient synthetic route to obtain gold containing anti-inflammatory drug candidates with balanced pro/anti-oxidative properties.